Prevention of Early Stunting Through Family Posyandu in Sape District, Bima Regency - Nasution, Buyung; Zainudin, Zainudin; Jaya, Ahmad (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2022)
Stunting is a condition marked when a child's length or height is less than their age or a condition in which a child experiences growth disorders that causes his body to be shorter than his peers which is the main cause of malnutrition. As an area with a fairly high stunting rate in West Nusa Tenggara Province, Sape District is currently carrying out various cross-sectoral efforts in order to maximize early prevention and treatment of stunting. The purpose of this study was to determine the role of Posyandu Family Cadres in early prevention and treatment of stunting in Sape District, Bima Regency. This research is a field research that examines empirical reality in society as a research object using a qualitative approach. While the method of data collection is done by interviews and observations using guidelines that have been prepared previously as a guide. The results of this study indicate that Family Posyandu Cadres have a strategic role and have a significant impact on stunting management. This is due to several reasons, including: 1) Family Posyandu cadres as the vanguard of basic health services in the community; 2) The interaction intensity of posyandu cadres is quite dominant compared to other health workers; 3) Almost even distribution of Posyandu cadres in every region to remote areas; and 4) There is a moral responsibility carried by the Posyandu Cadre if stunting occurs in a member of the surrounding community.